Transvaginal natural orifice transluminal endoscopic surgery for early-stage ovarian cancer and borderline ovarian tumors: a case series - Kellerhals, Gaétan; Nef, James; Hurni, Yannick; Huber, Daniela (Frontiers in Surgery, 2025)
IntroductionSurgery is the cornerstone of ovarian cancer treatment. Transvaginal natural orifice transluminal endoscopic surgery (vNOTES) is a novel, minimally invasive technique that is gaining interest in gynecological oncology. However, its use in ovarian cancer is still limited, with only a few cases reported. This study aimed to evaluate the feasibility of vNOTES for the surgical staging of borderline and early-stage ovarian cancer.MethodsWe retrospectively reviewed all cases of borderline ovarian tumors (BOTs) and early-stage ovarian cancer surgically staged by vNOTES at our institution between October 2021 and August 2024.ResultsEleven patients were included, seven with early-stage ovarian or tubal cancer and 4 with BOTs. The median age was 47 (27–81) years, and the median body mass index was 28.1 (22.4–39.2) kg/m2. Complete vNOTES staging was achieved in all cases, including peritoneal washing, unilateral/bilateral salpingo-oophorectomy, abdominal cavity inspection, peritoneal biopsies, infracolic omentectomy, and total hysterectomy when required. The median operating time was 70 (35–138) min, with a median blood loss of 50 (10–100) ml. No intraoperative complications occurred except for one case of minor ovarian spillage. No conversions to conventional laparoscopy or laparotomy were needed. Postoperative complications included one surgical site infection (9.1%) and 2 cases of postoperative cystitis (18.2%). No severe complications graded ≥3 on the Clavien-Dindo classification were observed.ConclusionvNOTES appears to be a feasible approach for the surgical staging of highly selected patients with early-stage adnexal malignancies. Further studies are needed to validate its long-term safety and oncological outcomes.